THE RELATIONSHIP BETWEEN TEACHERS TEACHING VARIATIONS AND ELEMENTARY SCHOOL STUDENTS SCIENCE LEARNING OUTCOMES - Sudirman Sudirman; Muhammad Awal Nur; Andi Yustika Sari (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2026)
Primary education is the main foundation in character building and developing the potential of students. Therefore, the learning process needs to be designed in a comprehensive, meaningful, and enjoyable manner in order to foster students' motivation to learn. This study aims to determine whether there is a relationship between teachers' skills in varying their teaching methods and the learning outcomes of Natural and Social Sciences (IPAS) subjects in senior classes at SDN 77 Pallae, Bone Regency. This study uses a quantitative approach with a population of 52 students. Samples were taken using saturated sampling techniques. The data were analysed using the Pearson Product-Moment technique. The results of the inferential statistical analysis showed a significance value of 0.001 < 0.05 with a correlation coefficient of 0.454, which is in the moderate category. These findings indicate that there is a positive and significant relationship between teachers' skills in implementing teaching variations and the IPAS learning outcomes of senior students at SDN 77 Pallae, Bone Regency.